NLRP1 influences the systemic sclerosis phenotype: a new clue for the contribution of innate immunity in systemic sclerosis-related fibrosing alveolitis pathogenesis. Issue 4 (13th December 2010) - Dieudé, P; Guedj, M; Wipff, J; Ruiz, B; Riemekasten, G; Airo, P; Melchers, I; Hachulla, E; Cerinic, M Matucci; Diot, E; Hunzelmann, N; Caramaschi, P; et al.
Abstract : Background: Recent evidence has highlighted a potential role of interleukin 1β (IL-1β) in systemic sclerosis (SSc). NLRP1 provides a scaffold for the assembly of the inflammasome that promotes the processing and maturation of pro-IL-1β. In addition, NLRP1 variants were found to confer susceptibility to autoimmune disorders. Objective: To study a possible association of the NLRP1 rs6502867, rs2670660 and rs8182352, rs12150220 and rs4790797 with SSc in the European Caucasian population. Methods: NLRP1 single nucleotide polymorphisms were genotyped in 3227 individuals comprising a discovery set (870 SSc patients and 962 controls) and a replication set including individuals from Germany (532 SSc patients and 324 controls) and Italy (527 SSc patients and 301 controls), all individuals being of European Caucasian origin. Results: Conditional analyses revealed a significant association for the NLRP1 rs8182352 variant with both anti-topoisomerase-positive and SSc-related fibrosing alveolitis (FA) subsets under an additive model: p=0.0042, OR 1.23 (95% CI 1.07 to 1.41) and p=0.0065 OR 1.19 (95% CI 1.05 to 1.36), respectively. Logistic regression analysis showed an additive effect of IRF5 rs2004640, STAT4 rs7574865 and NLRP1 rs8182352 risk alleles on SSc-related FA. Conclusions: Our results establish NLRP1 as a new genetic susceptibility factor for SSc-related pulmonary fibrosis and anti-topoisomerase-positive SSc phenotypes. This provides new insights into the pathogenesis of SSc, underlining the potential role of innate immunity in particular in the FA-positive SSc subphenotype, which represents a severe subset of the disease.